(untitled) (Journal of Medicine, 2013)
Purpose: The purpose of this study was to detect biofilm formation in clinical isolates of Acinetobacter species and to observe correlation between biofilm formation and antimicrobial resistance among Acinetobacter isolates. Methods: Two hundred fifty six clinical samples collected from patients who were admitted in Intensive Care Unit (ICU) and on device, patients from Surgery, Medicine, Gynae & Obs and Urology department of Bangabandhu Sheikh Mujib Medical University (BSMMU) and from Burn unit of Dhaka Medical College Hospital were included in this study. Biofilm formation and antibiotyping were performed for the isolates of Acinetobacter species recovered from clinical samples including tracheal aspirates, blood, urine, wound swab, pus, throat swab, endotracheal tubes, burn samples, ascitic fluid, sputum, aural swab, oral swab, cerebrospinal fluid, and catheter tip. Correlation of biofilm formation with antimicrobial resistance pattern among Acinetobacter isolates were also observed in this study. Result: A total of 256 various specimens were studied of which 95 Intensive Care Unit (ICU) and 161 Non ICU samples. Out of 95 ICU and 161 Non ICU samples, Acinetobacter species were isolated from 32 (33.7%) and 20(12.4%) respectively. From 32 ICU and 20 Non ICU Acinetobacter isolates, 28 (87.5%) and 11 (55%) were biofilm producers. Biofilm forming capacity of Acinetobacter species was significantly (p<0.008) greater in ICU than in Non ICU isolates. In both ICU and Non ICU isolates, biofilm forming Acinetobacter species were 100% resistant to amoxicillin, ceftriaxone, ceftazidime, cefotaxime, cefuroxime, and aztreonam. Resistance to antibiotics such as gentamicin, amikacin, netilmicin, ciprofloxacin and imipenem was higher among biofilm forming Acinetobacter isolates in ICU than Non ICU isolates. Susceptibility to colistin was 100% in Non ICU isolates but in ICU it showed 7.1% resistance. Conclusions: This investigation showed that most of the clinical isolates of Acinetobacter species were biofilm producers especially from ICU samples and they were multidrug resistant. Even polymixin resistant Acinetobacter isolates are slowly emerging. This is very alerming for us that biofilm forming multidrug resistant Acinetobacter species represents a severe threat in the treatment of hospitalized patients. So, antibiotic policy and guidelines are essential to eliminate major outbreak in future. DOI: http://dx.doi.org/10.3329/jom.v14i1.14533 J MEDICINE 2013; 14 : 28-32